Stomatal size and frequency in wild (A. webbii) and cultivated (A. communis) almonds - Palasciano M.; Camposeo S.; Godini A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Stomatal size and frequency are features commonly related to plant water stress tolerance. In general, size and number are negatively correlated and may vary greatly among species and genotypes. The number of stomata per leaf area unit is considered a peculiar characteristic of species and plant varieties. In order to provide information concerning this topic, a study was carried out on the stomata size and frequency of 15 cultivated almonds (A. communis) and 5 Apulian wild almonds (A. webbii). The varieties of A. communis were chosen taking into consideration their country of origin (extra Mediterranean/Mediterranean/Apulian), shell hardness (paper/hard) and kernel taste (sweet/bitter). The only evident difference between the cultivated and wild almonds concerned the leaf area; stomata frequency and size were independent of other characteristics, such as origin, country of origin, shell hardness and kernel taste of the twenty varieties/seedlings investigated.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)